Confessions of a maddog : a romp through the high-flying Texas music and literary era of the fifties to the seventies - Milner, Jay Dunston, 1923-2011 (University of North Texas Press, 1998)
Once upon a time there was an innocent lad from West Texas who wrote a novel and fell in with a rabble of Texas writers as they were bridging the literary gap between J. Frank Dobie and his paisanos and the current bumper crop of Texas writers who seem to be everywhere writing about everything. This rowdy rabble of gap bridgers bonded in a sort of literary and social club they called Maddog Inc. (Motto: Doing indefinable services to mankind.) But our hero managed to live through it all anyway. This is his story.